184 Cardioprotective Role of Hexarelin in a Mouse Model of Myocardial Infarction. (3rd June 2016) - McDonald, Hayley; Peart, Jason; Kurniawan, Nyoman; Galloway, Graham; Samuel, Chrishan; Chen, Chen
Abstract : This study aimed to determine whether Hexarelin (HEX), a synthetic growth hormone secretagogue, preserves cardiac function and attenuates remodelling in mouse models of myocardial infarction. Myocardial ischemia was induced by ligation of the left descending coronary artery in C57BL/6J mice followed by HEX (n = 16) or vehicle (VEH) (n = 16) administration at 0.3 mg/kg/day for 21 days. Treated and Sham mice were subjected to magnetic resonance imaging using a T1 -weighted late gadolinium enhancement sequence (LGE) at 9.4 Tesla (T) to measure left ventricular (LV) function, mass and infarct size at 24hrs and 21 days. HEX mice demonstrated a significant improvement (P < 0.05) in ejection fraction (EF) compared with VEH at 24 h (42% vs 34% respectively) and at 21 days (49% vs 36%). A significant decrease in LV mass, interstitial collagen and collagen concentration was demonstrated after 21 days within the HEX group. This was accompanied by a decrease in TGF-Î²1 and Î ± -SMA and increase in MMP-13 in the HEX group. Furthermore, heart rate variability analysis demonstrated that HEX treatment shifted the balance of autonomic nervous activity towards a parasympathetic predominance, evidenced by a smaller low/high-frequency power ratio and increased normalised high frequency power. This was combined with a significant decrease in Troponin-I, IL1- Î² and TNF-Î ± levels with HEX treatment compared with VEH treatment after 24 h. These results demonstrate that GHS may preserve ventricular function and favourably remodel the process of fibrotic healing in mouse models of myocardial infarction; this may be through anti-inflammatory mechanisms.